Someplace to Call Home - Dallas, Sandra (Ann Arbor, MI : Sleeping Bear Press, 2019)
In 1933, when twelve-year-old Hallie Turner and her brothers, Tom and Benny, take to the road seeking whatever work they can get, they find kindness in small-town Kansas.
Keywords: Dust Bowl Era, 1931-1939 -- Juvenile fiction; Depressions -- Juvenile fiction -- 1929; Nineteen thirties -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Poverty -- Juvenile fiction; Dust Bowl Era, 1931-1939 -- Fiction; Depressions -- Fiction -- 1929; Brothers and sisters -- Fiction; Orphans -- Fiction; Poverty -- Fiction; Kansas -- Juvenile fiction; Kansas -- Fiction; Historical fiction